Representasi Gaya Bahasa Sindiran pada Webtoon Trickster sebagai Media Pembelajaran Komik Strip Teks Anekdot di SMA - Imatriya Nur Jannah; Jendriadi; Yanti Sariasih (Universitas Muria Kudus, 2026)
Satire language style in literary works can be used as a medium for conveying social criticism. The purpose of this study is to identify and analyze the satire used in the Webtoon